O bloqueio geográfico injustificado - Ferreira, Inês de Castro Amorim (2021)
Considering the relatively low level of cross-border transactions in the EU, particularly in e-commerce sector, which prevent full use of the growth potential of european internal market, EC recognizes the urgency to effectively tackle obstacles that artificially segment this market along internal borders and limit free circulation of goods and services. In particular, Regulation (EU) 2018/302 is issued to prevent unjustified geo-blocking, a discriminatory digital tool used by european traders aiming consumers and businesses (in particular, small and medium-sized ones) based directly or indirectly on their nationality, place of residence or establishment, which, using user's location, leads to (i) the refusal to access a website; (ii) automatic forwarding to another website without prior consent; (iii) refusing the sale; and (iv) changing the terms and conditions and/or prices charged. This investigation aims to critically analyze problems and competitive effects of unjustified geo-blocking practices, their context and need for regulation, the efforts of the european legislator and EC decisions regarding this matter and, finally, the issues raised regarding Competition Law.